(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Una premessa di metodo - 2. Giustizia limiti e sacralità del “fine vita” - 3. Tra indisponibilità della vita e diritto di autodeterminazione individuale. La prospettiva della Corte EDU … - 4. … e le prudenti soluzioni del diritto italiano tra leggi e prassi giurisprudenziale - 5. Considerazioni conclusive: esiste la libertà di congedarsi dal mondo? The experience of pain and the reasons for hope. Reflections on the end of life of postmodern man ABSTRACT: The surprising development of biotechnology, new knowledge and unprecedented possibilities of intervention on human beings, have strongly affected the natural events of being born and dying, bringing out new rights and new instances of protection, aimed at ensuring respect for individual self-determination and human dignity in the face of the increasingly pressing intrusiveness of science and technology. Nonetheless, these possibilities offered by science may, for some, not coincide with the ideal conception of life and human dignity, since these are interventions capable of prolonging survival in often very critical conditions, not always adequate to guarantee a life worth living. At this point, the question is whether there is a way to pursue a harmonious composition between the concepts of life and human dignity, in the extreme variety of cases where there is a question of their protection, especially with regard to end-of-life issues.